Benin : 2006 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that economic performance of Benin has been relatively subdued since 2003 after a decade of high growth. Slow economic growth has reflected limited progress in addressing core economic vulnerabilities and delays in implementing crucial growth-supporting structural reforms, against a backdrop of an appreciating real effective exchange rate and, more recently, a sizable deterioration in the terms of trade. Notwithstanding further delays in structural reforms, a turnaround in cotton production is helping to revive growth in 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet